Does varying resistance exercises promote superior muscle hypertrophy and strength gains? A systematic review - Kassiano, W.; Nunes, J. P.; Costa, B.; Ribeiro, A. S.; Schoenfeld, B. J.; Cyrino, E. S. (The Journal of Strength and Conditioning Research, 2022)
Fitness professionals routinely employ a variety of resistance training exercises in program design as a strategy to enhance muscular adaptations. However, it remains uncertain whether such an approach offers advantages over a fixed-exercise selection. The objective of this review was to review the effects of exercise variation on muscle hypertrophy and strength. A search of the literature was conducted using PubMed/MEDLINE, Scopus, and Web of Science databases. Eight studies were identified as meeting inclusion criteria. The combined total sample of the studies was N = 241, comprising all young men. The methodological quality of included studies was considered "good" and "excellent" based on the Physiotherapy Evidence Database Scale. The available studies indicate that varying exercise selection can influence muscle hypertrophy and strength gains. Some degree of systematic variation seems to enhance regional hypertrophic adaptations and maximize dynamic strength, whereas excessive, random variation may compromise muscular gains. We conclude that exercise variation should be approached systematically with a focus on applied anatomical and biomechanical constructs; on the contrary, employing different exercises that provide a redundant stimulus, as well as excessive rotation of different exercises (i.e., high frequency of change), may actually hinder muscular adaptations.